Recycling and collaging: the roles of composer and performer inside a collaborative creation process (Per Musi, 2012)
This article analyzes the interconnection between composer and performer inside a collaborative creationprocess. In this process, exemplified through the Edson Zampronha’s work Recycling Collaging Sampling, the interaction between both roles results in a work which sense of belonging and authorship are equally shared.